2015
DOI: 10.1016/j.jcin.2015.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Triple Antithrombotic Therapy Following Anterior ST-Segment Elevation Myocardial Infarction

Abstract: Fernandez-Portales J. Limitation to the utilization of the new antiplatelet agents in acute coronary syndromes related with patient's characteristics. Rev Esp Cardiol 2015;68:448-50. 5. Wittfeldt A, Emanuelsson H, Brandrup-Wognsen G, et al. Ticagrelor enhances adenosine-induced coronary vasodilatory responses in humans. J Am Coll Cardiol 2013;61:723-7. REPLY: Lights and Shadows of Antiplatelet Therapy in Primary Percutaneous Coronary Intervention We thank Lozano et al. for their thoughtful comments on our ETAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Despite early reports of the benefits of adding anticoagulation to standard therapy for patients with anterior MI 15 – 17 , no study that has included PCI patients has demonstrated an advantage of TATT 8 , 18 – 22 . Moreover, despite a recent report that the incidence of LVT following pPCI is not negligible 23 , Le May et al .’s propensity-matched retrospective single-center analysis suggested a higher incidence of NACE with TATT compared with clopidogrel-based DAPT 8 , 24 . Recently, in a mixed pPCI and pharmacoinvasive population, Shavadia et al .…”
Section: Discussionmentioning
confidence: 99%
“…Despite early reports of the benefits of adding anticoagulation to standard therapy for patients with anterior MI 15 – 17 , no study that has included PCI patients has demonstrated an advantage of TATT 8 , 18 – 22 . Moreover, despite a recent report that the incidence of LVT following pPCI is not negligible 23 , Le May et al .’s propensity-matched retrospective single-center analysis suggested a higher incidence of NACE with TATT compared with clopidogrel-based DAPT 8 , 24 . Recently, in a mixed pPCI and pharmacoinvasive population, Shavadia et al .…”
Section: Discussionmentioning
confidence: 99%